2005
DOI: 10.1016/j.femsle.2005.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of enantioselective ester hydrolase fromBacillus pumilusDBRL-191

Abstract: A gene from Bacillus pumilus expressed under its native promoter was cloned in Escherichia coli. Recombinant B. pumilus esterase (BPE) affects the kinetic resolution of racemic mixtures such as unsubstituted and substituted 1-(phenyl)ethanols (E approximately 33-103), ethyl 3-hydroxy-3-phenylpropanoate (E approximately 45-71), trans-4-fluorophenyl-3-hydroxymethyl-N-methylpiperidine (E approximately 10-13) and ethyl 2-hydroxy-4-phenylbutyrate (E approximately 7). The enzyme is composed of a 34-amino acid signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Even the lipases showing 98% similarity at the amino acid level displayed different biochemical properties among each other. The enzyme in the present study was optimally active at pH 8 and stable at pH 7-9.5 which is similar to lipases from B. subtilis [Ma et al, 2006] and B. pumilus DBRL-191 [Rasool et al, 2005] but in variation with B. pumilus [Ruiz et al, 2003] and B. megaterium [Ruiz et al, 2002] as these have pH optima of 7 and pH stability from 7 to 12. The purified lipase demonstrated a temperature optimum of 35 ° C which was similar to the lipase of B. pumilus DBRL-191 [Rasool et al, 2005] but contrary to lipases produced by B. pumilus [Ruiz et al, 2003] and B. megaterium [Ruiz et al, 2002] as they demonstrated optimal activity at 45 ° C. These results imply that there are some functional differences between the JklipWT gene product and other lipases of this family in spite of the significant amino acid sequence similarity.…”
Section: Discussionsupporting
confidence: 65%
“…Even the lipases showing 98% similarity at the amino acid level displayed different biochemical properties among each other. The enzyme in the present study was optimally active at pH 8 and stable at pH 7-9.5 which is similar to lipases from B. subtilis [Ma et al, 2006] and B. pumilus DBRL-191 [Rasool et al, 2005] but in variation with B. pumilus [Ruiz et al, 2003] and B. megaterium [Ruiz et al, 2002] as these have pH optima of 7 and pH stability from 7 to 12. The purified lipase demonstrated a temperature optimum of 35 ° C which was similar to the lipase of B. pumilus DBRL-191 [Rasool et al, 2005] but contrary to lipases produced by B. pumilus [Ruiz et al, 2003] and B. megaterium [Ruiz et al, 2002] as they demonstrated optimal activity at 45 ° C. These results imply that there are some functional differences between the JklipWT gene product and other lipases of this family in spite of the significant amino acid sequence similarity.…”
Section: Discussionsupporting
confidence: 65%
“…The expression of Bacillus lipase led to the formation of inclusion bodies in E. coli host [36]. However, Rasool et al [37] showed the expression of DBRL-191 lipase in cytoplasm without inclusion body formation. Our results suggested that the formation of inclusion bodies occurred due to high level of expression under the T7 promoter and high hydrophobicity of the protein.…”
Section: Effect Of Temperature On Growth and Induction Of Proteasementioning
confidence: 99%
“…There has been an increasing awareness of the enormous potential of microorganisms and enzymes for the transformation of synthetic chemicals with high chemoselectivity, regioselectivity, stereoselectivity, and specificity (Patel, 2002). Large numbers of microorganisms or enzymes have been employed for the production of optically active compounds by means of kinetic resolution or stereospecific chemical transformations (Rasool et al, 2005).…”
Section: Biotransformation (Biocatalysis)mentioning
confidence: 99%